Whole‐Voltage‐Range Oxygen Redox in P2‐Layered Cathode Materials for Sodium‐Ion Batteries. Issue 13 (1st March 2021) - Li, Xun‐Lu; Wang, Tian; Yuan, Yifei; Yue, Xin‐Yang; Wang, Qin‐Chao; Wang, Jun‐Yang; Zhong, Jun; Lin, Ruo‐Qian; Yao, Yuan; Wu, Xiao‐Jing; Yu, Xi‐Qian; Fu, Zheng‐Wen; et al.
Abstract: Oxygen‐redox of layer‐structured metal‐oxide cathodes has drawn great attention as an effective approach to break through the bottleneck of their capacity limit. However, reversible oxygen‐redox can only be obtained in the high‐voltage region (usually over 3.5 V) in current metal‐oxide cathodes. Here, we realize reversible oxygen‐redox in a wide voltage range of 1.5–4.5 V in a P2‐layered Na0.7 Mg0.2 [Fe0.2 Mn0.6 □0.2 ]O2 cathode material, where intrinsic vacancies are located in transition‐metal (TM) sites and Mg‐ions are located in Na sites. Mg‐ions in the Na layer serve as "pillars" to stabilize the layered structure during electrochemical cycling, especially in the high‐voltage region. Intrinsic vacancies in the TM layer create the local configurations of "□–O–□", "Na–O–□" and "Mg–O–□" to trigger oxygen‐redox in the whole voltage range of charge–discharge. Time‐resolved techniques demonstrate that the P2 phase is well maintained in a wide potential window range of 1.5–4.5 V even at 10 C. It is revealed that charge compensation from Mn‐ and O‐ions contributes to the whole voltage range of 1.5–4.5 V, while the redox of Fe‐ions only contributes to the high‐voltage region of 3.0–4.5 V. The orphaned electrons in the nonbonding 2 p orbitals of O that point toward TM‐vacancy sites are responsible for reversible oxygen‐redox, and Mg‐ions in Na sites suppress oxygen release effectively. Abstract : Na0.7 Mg0.2 [Fe0.2 Mn0.6 □0.2 ]O2 with native transitional metal (TM) vacancies is designed as a novel cathode material for sodium‐ion batteries. The TM vacancies lead to nonbonding O 2p orbitals in this material, pointing toward these vacancies triggering reversible whole‐voltage‐range oxygen redox during charge and discharge processes. This work provides new ideals for design of cathode materials in anionic redox chemistry.